Shifting Patterns of Hepatitis C Transmission in Duhok: The Emerging Role of Injection Drug Use and a Warning Signal for Iraq - Hussein, Nawfal R; Abozait, Halder; Mosa, Ahmed (Eastern Journal of Medical Sciences, 2025)
Hepatitis C virus (HCV) remains a significant public health concern globally, especially in low- and middle-income countries such as Iraq. In Iraq, while blood transfusion has historically been the main route of HCV transmission, recent observations in Duhok City suggest a growing shift toward injection drug use (IDU) as an emerging and increasingly dominant risk factor. This shift marks a critical public health turning point, as newly diagnosed HCV cases are now frequently associated with a history of injecting drugs. The rise in IDU raises concerns due to its strong association with bloodborne infections, including HCV, HBV, and HIV, as well as various systemic barriers to care, such as legal restrictions, stigma, lack of harm reduction services, and centralized healthcare delivery. Despite these challenges, highly effective and affordable treatments for HCV exist, and studies show similar cure rates among people who inject drugs compared to the general population. To mitigate the emerging threat, the article calls for comprehensive, evidence-based interventions such as harm reduction services, decentralized HCV care, public education, and enhanced surveillance. Addressing IDU-linked HCV transmission now is essential to prevent a larger epidemic and align with WHO’s 2030 elimination goals.